2006
DOI: 10.1007/s00412-006-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific proximity of centromeric domains of one homologue each of chromosomes 2 and 11 in nuclei of cerebellar Purkinje neurons

Abstract: In Purkinje neurons of the mouse cerebellum, the centromeres of several chromosomes are placed in close proximity to form a distinct pattern of clusters and exhibit reproducible spatial redistributions during development. In granule neurons, an adjacent cell type in the cerebellum, the pattern, size, and number of centromeric aggregations are different from those of Purkinje neurons. The present work was undertaken to test the hypothesis that the same chromosomes form part of one aggregate in a cell-type-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Previous work has shown that centromeres of chromosomes 2 and 11 were detected in close proximity in Purkinje neurons [11]. The results of the present work show that the additional chromosomes that contribute their centromeres to the same cluster that contains centromeres of chromosomes 2 and 11 vary.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Previous work has shown that centromeres of chromosomes 2 and 11 were detected in close proximity in Purkinje neurons [11]. The results of the present work show that the additional chromosomes that contribute their centromeres to the same cluster that contains centromeres of chromosomes 2 and 11 vary.…”
Section: Discussionsupporting
confidence: 61%
“…2). We have previously reported the routine clustering of chromosome pairs 2 and 11 in Purkinje neurons [11]. In contrast to this, pairs 2&3, 2&8 and 6&8 routinely did not show clustering of centromeres.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations